Fenomena Pengobatan Melalui Pendekatan Tasawuf: Studi Kasus Praktek Pengobatan Nek Mas di Kecamatan Tungkal Jaya Provinsi Sumatera Selatan (SUNGKAI: Jurnal Aqidah dan Filsafat Islam, 2024)
This study examines the phenomenon of treatment through a Sufism approach with a case study of treatment practices carried out by Nek Mas in Tungkal Jaya District, South Sumatra Province. Sufism, as a branch of the Islamic tradition, emphasizes the process of purification of the soul and a spiritual approach to God. The values of Sufism that focus on spiritual awareness, dhikr, and contemplation are applied by Nek Mas in the form of alternative medicine that is believed to be able to cure various diseases, both physical and mental. In practice, the treatment involves spiritual components such as prayer, dhikr, and meditation that are intended to bring peace of mind and harmony between body and spirituality. This study uses a qualitative approach with a case study method to gain an understanding of the background, methods, and beliefs that underlie the practice of Nek Mas treatment. The results of the study show that Nek Mas treatment is widely accepted by the local community because it is considered more in accordance with existing spiritual and cultural values. Treatment through the Sufism approach is also considered effective in dealing with various diseases, especially those believed to be related to spiritual disorders. The study concludes that the Islamic mysticism approach to medicine can be an effective alternative, especially in the context of societies with strong religious beliefs.